USING INSTAGRAM TO IMPROVE STUDENTS WRITING SKILL OF RECOUNT TEXT AT THE ELEVENTH GRADE OF MAS PAB 2 HELVETIA MEDAN - Ayuning Tias, Lita (BRIGHT VISION Journal of Language and Education, 2021)
This research was aimed to find out the improving of the students’ writing skill of recount text by using Instagram. The subject of this research were the eleventh grade of MAS PAB 2 Helvetia Medan which consisted of 35 students. This research applied classroom action research. The data of this research were qualitative and quantitative data and the instruments of collecting data were used such as: Pre-test and Post-test, interview sheet, observation sheet, and photography evidence. The quantitative data were taken from the test. The test was given to the students in form of pretest, post test in the first cycle, and the post-test in the second cycle. The result of the analyzing the data showed that there was an improving on the students’ writing skill from each cycles. It was showed from the mean of pre-test was 69. Where, there were 12 student got successfull score criteria or it was only 34,2% and 23 students’ got unsuccessful or it was 65,7 %. After doing cycle I by using Instagram, there was an improving of the result of the students’ mean was 73. Where, 17 students got successful criteria score or it was only 48,5% and 18 students’ got unseccessful criteria score or it was 51,4%. Then doing repairing for second cycle after reflection on the first cycle, there was improving of students’ mean was 78. Where, 27 students’ got successful criteria score or it was 77,1% and  8 students’ got unsuccessful criteria score or it was 22,8%. In other words, it could be concluded that the use of Instagram improved the students’ writing skill and their interest in writing.Keywords: Writing, Recount text, Instagram, Improvement